2017
DOI: 10.5530/ijper.51.3s.4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ginger Extract and Diazepam on Anxiety Reduction in Animal Model

Abstract: Objective: Anxiety disorders are from common disorders of human. Drug treatments have side effects, and searching new ways with fewer side effects is inevitable. Ginger is a medicinal plant with many therapeutic effects. Methods: In current study the effects of ginger extract and diazepam on anxiety reduction of laboratory mice were investigated. Sixty female mice (25-30g) were divided into six groups including control, anxiety, diazepam and 50, 100 and 200 mg/kg extract doses. After receiving the last dose, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 3 publications
(2 reference statements)
2
10
0
Order By: Relevance
“…3 Ginger extract was as effective as diazepam in reducing anxiety. 4 and its pattern of behavior in the forced swimming test resemble that of serotonergic antidepressants. 5 The bioflavonoid quercetin is abundant in Ginger.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…3 Ginger extract was as effective as diazepam in reducing anxiety. 4 and its pattern of behavior in the forced swimming test resemble that of serotonergic antidepressants. 5 The bioflavonoid quercetin is abundant in Ginger.…”
Section: Introductionmentioning
confidence: 81%
“…The present behavioral findings in rats with the ginger extract demonstrating its anxiolytic-like effect in the elevated plus maze test (Table 3) confirm previous observations in mice. 4 Our studies are concerned mainly with the role of the serotonin system in anxiety and also in depression. That serotonin plays an important role in anxiety-related behavior and in the mechanisms of action of anxiolytics is well documented, 9 see also references cited therein, with serotonin receptors playing differential roles.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingto Perveenetal., (2009) Nigella sativa increases the level of 5-HT and thus decrease anxiety. Thymoquinone in Nigella sativa might also decrease nitric oxide and reverse decreased brain GABA content and give anxiolytic effect [18] Several studies indicate that anxiety and depressive disorders are not heterogeneous disorders, but rather share many common symptoms and pathogenic mechanisms [19] Also, a number of studies have evaluated the effects of inorganic mercury in the central nervous system and reported the presence of behavioral dysfunctions, in particular the anxiety and depression [20,21] In the current study, the forced swimming test (FST) indicates depressive behavior in rats treated with mercuric chloride. Pre-treatment with ginger extract and Nigella sativa alone and in combination enhanced swimming time, thereby reducing the immobility time in rats in FST, indicating antidepressant-like activity of this antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Ginger extract can remove disorders caused by oxidative stresses as a strong anti-oxidant. Studies have shown that extant phenolic compounds and anthocyanins including gingerols and the sugevals had many neuro protective effects such as analgesic effects, memory improvement, and learning caused by the aging process (Fadaki et al, 2017). For culinary purposes ginger is suitable for all dished both sweet such as drinks, puddings, apple pie, cakes, breads, candies, etc; and savoury such as soups, sauces, stews, savory puddings, grills, roasts, etc) (Oludoyin and Adegoke, 2014).…”
Section: Gingerglycolipidsmentioning
confidence: 99%